2020
DOI: 10.1002/jpen.1831
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Oil–Based Lipid Emulsions vs Soybean Oil–Based Lipid Emulsions on Incidence and Severity of Intestinal Failure–Associated Liver Disease in a Neonatal Intensive Care Unit

Abstract: Background Neonates requiring long‐term parenteral nutrition (PN) are at risk for developing intestinal failure–associated liver disease (IFALD). The purpose of this study was to compare the incidence and severity of IFALD in a highly surgical neonatal population receiving mixed oil–based lipid emulsions (MOLEs) vs soybean oil–based lipid emulsions (SOLEs) for long‐term PN. Methods This retrospective cohort study evaluated patients admitted to a neonatal intensive care nursery that received PN for ≥14 days. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…Interestingly, a recent study by Ferguson el al. looked at 107 patients in a retrospective cohort and found that 44.8% with intestinal failure developed PNAC while receiving SO-LE and only 30% of patients receiving MO-LE [ 68 ]. In their multivariate analysis they found that after adjustment for cofounding factors, the improved performance of MO-LE could not be attributed to the lipid emulsion.…”
Section: Lipid Emulsion Composition and Clinical Effectsmentioning
confidence: 99%
“…Interestingly, a recent study by Ferguson el al. looked at 107 patients in a retrospective cohort and found that 44.8% with intestinal failure developed PNAC while receiving SO-LE and only 30% of patients receiving MO-LE [ 68 ]. In their multivariate analysis they found that after adjustment for cofounding factors, the improved performance of MO-LE could not be attributed to the lipid emulsion.…”
Section: Lipid Emulsion Composition and Clinical Effectsmentioning
confidence: 99%
“…Whereas IFALD was initially considered as a PN complication, an increasing number of evidence suggests that liver disease is not solely due to PN administration but strongly related to IF factors ( 13 ). In addition to the components of PN, prematurity, history of multiple surgical procedures, recurrent sepsis, and the lack of enteral feeding are further known risk factors for the development of IFALD ( 14 ) ( Figure 1 ).…”
Section: Prevalence Etiology and Risk Factorsmentioning
confidence: 99%
“…Intravenous lipid emulsions, particularly when administered at high dose and based on soybean or safflower oil, are implicated in IFALD development ( 3 , 20 ). PN mode of administration and its duration also play a role ( 14 ). Although many risk factors are known, the identification of patients at heightened risk for IFALD progression still poses a considerable challenge due to possible evolution to liver cirrhosis of patients with normal liver enzymes and bilirubin values ( 21 ).…”
Section: Prevalence Etiology and Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations